On the issue of preconditions the introduction of sales tax in the tax system of the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
The study of indirect taxation issues at the present stage is of particularimportance, since taxes express the fiscal interests of the state. Judicious use canpositively influence the process of pricing and affect consumption patterns. Oneof the main problems in the area of taxation is to achieve the optimal valueof tax collection. Taxes are the primary vehicle through which the image ofthe state and local money funds. For any state, at whatever stage of theireconomic and social development, it may be, the need to increase budgetrevenues is one of the most urgent tasks. Finding the right solution to thisproblem is extremely important for Kazakhstan economy.Factors adversely affecting the collection of indirect taxes include: adecline in production, the heavy financial and economic position of enterprises,the growth of non-payment companies, the provision of a largenumber of exemptions and deferrals, the introduction of “zones of economicpreference” tax evasion.After analyzing After analyzing revenues of indirect taxes in the statebudget revenues shows that in the structure of tax payments the share ofindirect taxes decreased year by year, in 2013 the proportion was 30.0%,in 2014 – 26.6%, in 2015 – 22 , 7%, and the data shows the timeliness ofthe changes in tax legislation.
Keywords: taxation; the state budget; the tax system; value-added tax.